Radiocarbon age dating and quality evolution of seawater intruding beneath a freshwater lens - Pieter J. Stuyfzand; Philip R. Nienhuis; Vincent E.A. Post (Applied Geochemistry, 2025)

High-energy systems are underrepresented in global porewater studies of sandy beach aquifers - Gudrun Massmann; Janek Greskowiak; Julius Degenhardt; Bert Engelen; Moritz Holtappels; Rena Meyer; Mike Müller-Petke; Nils Moosdorf; Jutta Niggemann; Katharina Pahnke; Vincent Post; Anja Reckhardt; et al. (Estuarine, Coastal and Shelf Science, 2025)

Reactive transport modeling to reveal the impacts of beach morphodynamics, storm floods and seasonal groundwater recharge on the biogeochemistry of sandy subterranean estuaries - Stephan L. Seibert; Gudrun Massmann; Rena Meyer; Vincent E.A. Post; Janek Greskowiak (Advances in Water Resources, 2025)

Composition and distribution of the near-shore waters bordering the coral reefs of Aruba, Bonaire, and Curaçao in the Southern Caribbean - Fleur C. van Duyl; Vincent E.A. Post; Boris M. van Breukelen; Victor Bense; Petra M. Visser; Erik H. Meesters; Paul Koeniger; Mark J.A. Vermeij (Marine Pollution Bulletin, 2024)

Impact of mineral reactions and surface complexation on the transport of dissolved species in a subterranean estuary: Application of a comprehensive reactive transport modeling approach - Stephan L. Seibert; Gudrun Massmann; Rena Meyer; Vincent E.A. Post; Janek Greskowiak (Advances in Water Resources, 2024)

Island hydrogeology in the tropics: Constraining a 3D variable-density groundwater flow and solute transport model with geophysics - Eddie W. Banks; Saskia Noorduijn; Vincent E.A. Post; Tim Munday; Camilla Sorensen; Kevin Cahill; Phillip Jolly; Joanna Ellis; Adrian D. Werner; Okke Batelaan (Journal of Hydrology, 2024)

Redox-zoning in high-energy subterranean estuaries as a function of storm floods, temperatures, seasonal groundwater recharge and morphodynamics - Janek Greskowiak; Stephan L. Seibert; Vincent E.A. Post; Gudrun Massmann (Estuarine, Coastal and Shelf Science, 2023)

The DynaDeep observatory – a unique approach to study high-energy subterranean estuaries - Gudrun Massmann; Grace Abarike; Kojo Amoako; Felix Auer; Thomas H. Badewien; Cordula Berkenbrink; Michael Ernst Böttcher; Simone Brick; Iris Valeria Medina Cordova; Jairo Cueto; Thorsten Dittmar; Bert Engelen; et al. (Frontiers in Marine Science, 2023)
Subterranean estuaries are connective zones between inland aquifers and the open sea where terrestrial freshwater and circulating seawater mix and undergo major biogeochemical changes. They are biogeochemical reactors that modify groundwater chemistry prior to discharge into the sea. We propose that subterranean estuaries of high-energy beaches are particularly dynamic environments, where the effect of the dynamic boundary conditions propagates tens of meters into the subsurface, leading to strong spatio-temporal variability of geochemical conditions. We hypothesize that they form a unique habitat with an adapted microbial community unlike other typically more stable subsurface environments. So far, however, studies concerning subterranean estuaries of high-energy beaches have been rare and therefore their functioning, and their importance for coastal ecosystems, as well as for carbon, nutrient and trace element cycling, is little understood. We are addressing this knowledge gap within the interdisciplinary research project DynaDeep by studying the combined effect of surface (hydro- and morphodynamics) on subsurface processes (groundwater flow and transport, biogeochemical reactions, microbiology). A unique subterranean estuary observatory was established on the northern beach of the island of Spiekeroog facing the North Sea, serving as an exemplary high-energy research site and model system. It consists of fixed and permanent infrastructure such as a pole with measuring devices, multi-level groundwater wells and an electrode chain. This forms the base for autonomous measurements, regular repeated sampling, interdisciplinary field campaigns and experimental work, all of which are integrated via mathematical modelling to understand and quantify the functioning of the biogeochemical reactor. First results show that the DynaDeep observatory is collecting the intended spatially and temporally resolved morphological, sedimentological and biogeochemical data. Samples and data are further processed ex-situ and combined with experiments and modelling. Ultimately, DynaDeep aims at elucidating the global relevance of these common but overlooked environments.

Distribution of tritium-helium groundwater ages in a large Cenozoic sedimentary basin (North German Plain) - Annika Desens; Georg Houben; Jürgen Sültenfuß; Vincent Post; Gudrun Massmann (Hydrogeology Journal, 2023)
The travel time of groundwater plays a major role in the understanding of hydrogeological systems; however, large data sets necessary for regional studies of groundwater age are rare. In this study, a unique large data set of groundwater samples analysed for tritium and helium isotopes collected over the last 20 years from Cenozoic aquifers of the North German Plain is explored. Hereby, the variety of natural and technical influences on the tritium-helium age, including screen depth and length, groundwater recharge rate and climatic effects, are investigated. To a sampling depth of ~40 m below ground level, the median tritium-helium age increases almost linearly with depth, reaching a maximum of 40 years. Below, the portion of older, tritium-free water rises. The tritium-helium ages of the tritium-bearing portion increase only slightly to a maximum of about 46 years. The depth distribution of the tritium-helium age shows a dependency on groundwater recharge rates. Considering the same depth level, younger ages are related to higher groundwater recharge rates as compared to groundwater that infiltrated in areas with lower recharge rates. This is especially observed for shallow depths. Tritium-helium ages younger than 40 years are reflected well in the atmospheric tritium input curves, while deviations from it can be related to anthropogenic influences such as input from nuclear power plants and irrigation with deep, tritium-poor groundwater. The regional distribution for shallow wells indicates increasing tritium-helium ages from west to east, corresponding to decreasing groundwater recharge rates due to the more continental climate in the east.

Experimental observations of aquifer storage and recovery in brackish aquifers using multiple partially penetrating wells - Lilli Witt; Moritz J. Müller; Maike Gröschke; Vincent E. A. Post (Hydrogeology Journal, 2021)
Aquifer storage and recovery systems using multiple partially penetrating wells (MPPW-ASR) can form a viable solution to the problem of freshwater buoyancy when using brackish aquifers for freshwater storage. This study presents the result of a series of laboratory experiments that aimed at visualizing the shape of freshwater bodies injected into a brackish aquifer and determining the effect on the recovery efficiency (RE) of several MPPW-ASR operational variables. A model aquifer was built in a Plexiglas tank using glass beads and water was injected and abstracted through point and vertical wells, which were operated in various combinations. Numerical models were used to support the interpretation of the time-lapse photographs, and showed that three-dimensional flow effects had to be considered for a correct interpretation of the visible dye patterns. Upward migration of both fresh (during injection) and brackish water (during recovery) along the vertical wells was observed, indicating that the role of well infrastructure as conduits is a critical design criterion for real-world systems. Gravitational instabilities formed when freshwater did not extend all the way to the top of the aquifer, and this negatively impacted the RE by causing greater mixing. The positive freshwater buoyancy led to freshwater bodies that became narrower with depth, and the formation of thin, elongated buffer zones along the aquifer top in multicycle experiments. Up-coning below abstraction wells resulted in lower RE values, reinforcing the potential of scavenger wells to enhance MPPW-ASR system performance.

Evaporation loss along the Calueque-Oshakati Canal in the Cuvelai-Etosha Basin (Northern Namibia): evidence from stable isotopes and hydrochemistry - Paul Koeniger; Josefina Hamutoko; Vincent E. A. Post; Matthias Beyer; Marcel Gaj; Thomas Himmelsbach; Heike Wanke (Isotopes in Environmental and Health Studies, 2021)

Future-proofing hydrogeology by revising groundwater monitoring practice - Gabriel C. Rau; Mark O. Cuthbert; Vincent E. A. Post; Daniel Schweizer; R. Ian Acworth; Martin S. Andersen; Philipp Blum; Elisabetta Carrara; Todd C. Rasmussen; Shemin Ge (Hydrogeology Journal, 2020)
Groundwater is an important global resource and its sustainable use faces major challenges. New methods and advances in computational science could lead to much improved understanding of groundwater processes and subsurface properties. A closer look at current groundwater monitoring practice reveals the need for updates with a special focus on the benefits of high-frequency and high-resolution datasets. To future-proof hydrogeology, this technical note raises awareness about the necessity for improvement, provides initial recommendations and advocates for the development of universal guidelines.

The intertidal springs near the Vergulde Draak 1656 wreck site, Western Australia: hydrogeological characteristics and archaeological significance - Vincent E. A. Post; Ursula Salmon; Wendy van Duivenvoorde (Hydrogeology Journal, 2020)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Annotated translation of “Nota in verband met de voorgenomen putboring nabij Amsterdam [Note concerning the intended well drilling near Amsterdam]” by J. Drabbe and W. Badon Ghijben (1889) - Vincent E. A. Post (Hydrogeology Journal, 2018)

Celebrating 50 years of SWIMs (Salt Water Intrusion Meetings) - Vincent E. A. Post; Gualbert Oude Essink; Adam Szymkiewicz; Mark Bakker; Georg Houben; Emilio Custodio; Clifford Voss (Hydrogeology Journal, 2018)

What is the Ghijben-Herzberg principle and who formulated it? - Vincent E. A. Post; Georg J. Houben; Joeri van Engelen (Hydrogeology Journal, 2018)

Groundwater flow in the transition zone between freshwater and saltwater: a field-based study and analysis of measurement errors - Vincent E. A. Post; Eddie Banks; Miriam Brunke (Hydrogeology Journal, 2018)

Detecting inter-aquifer leakage in areas with limited data using hydraulics and multiple environmental tracers, including 4He, 36Cl/Cl, 14C and 87Sr/86Sr - Stacey C. Priestley; Daniel L. Wohling; Mark N. Keppel; Vincent E. A. Post; Andrew J. Love; Paul Shand; Lina Tyroller; Rolf Kipfer (Hydrogeology Journal, 2017)

The first field-based descriptions of pumping-induced saltwater intrusion and upconing - Georg Houben; Vincent E. A. Post (Hydrogeology Journal, 2017)

Influence of model conceptualisation on one-dimensional recharge quantification: Uley South, South Australia - Carlos M. Ordens; Vincent E. A. Post; Adrian D. Werner; John L. Hutson (Hydrogeology Journal, 2014)

Review: Hydraulic head measurements—new technologies, classic pitfalls - Vincent E. A. Post; Jos R. von Asmuth (Hydrogeology Journal, 2013)

Editor’s Message: Hydrogeology education, textbooks and ‘Foundations’ articles - Vincent E. A. Post (Hydrogeology Journal, 2013)

Groundwater recharge to a sedimentary aquifer in the topographically closed Uley South Basin, South Australia - Carlos M. Ordens; Adrian D. Werner; Vincent E. A. Post; John L. Hutson; Craig T. Simmons; Benjamin M. Irvine (Hydrogeology Journal, 2012)

Preface: Saltwater and freshwater interactions in coastal aquifers - Vincent Post; Elena Abarca (Hydrogeology Journal, 2010)

Free convective controls on sequestration of salts into low-permeability strata: insights from sand tank laboratory experiments and numerical modelling - Vincent E. A. Post; Craig T. Simmons (Hydrogeology Journal, 2010)

Rates of salinization by free convection in high-permeability sediments: insights from numerical modeling and application to the Dutch coastal area - Vincent E. A. Post; Henk Kooi (Hydrogeology Journal, 2003)